Keeping a Critical Eye on Majority Language Influence: The Case of Uptalk in Heritage Spanish - Ji Young Kim; Gemma Repiso-Puigdelliura (Languages, 2021)
The goal of this study is to highlight the importance of taking into account variations in monolingual grammars before discussing majority language influence as a possible source of heritage speakers’ divergent grammars. In this study, we examine the production of uptalk in Spanish by heritage speakers of Mexican Spanish in Southern California. Uptalk (i.e., rising intonation contour at the end of a non-question utterance) is frequently associated with California English. Thus, heritage speakers’ use of uptalk is often considered to be influenced from English intonation (i.e., the majority language). Although uptalk in Spanish is not well understood, it has been observed in Mexican Spanish, which calls attention to the importance of investigating uptalk in monolingual Spanish. Using a dyadic interaction task, we obtained spontaneous speech data of 16 heritage speakers and 16 monolingual speakers of Mexican Spanish and compared the phonological and phonetic properties of uptalks produced by the two groups. Our results demonstrated that the heritage speakers and the monolingual speakers produced uptalks with similar frequencies and mainly used L+H* HH% and L* HH% contours. However, the two groups had more differences than similarities. Specifically, heritage speakers’ uptalks presented less dynamic contours and were produced with flatter rises than monolinguals’ uptalks. Heritage speakers’ divergent patterns showed close resemblance with patterns in English, suggesting majority language influence as a valid source of divergence. We discuss possible avenues for future research for a better understanding of the role of majority language influence on heritage Spanish uptalk.